10(x-4)=4(x+4)+4(x-2)

Simple and best practice solution for 10(x-4)=4(x+4)+4(x-2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 10(x-4)=4(x+4)+4(x-2) equation:



10(x-4)=4(x+4)+4(x-2)
We move all terms to the left:
10(x-4)-(4(x+4)+4(x-2))=0
We multiply parentheses
10x-(4(x+4)+4(x-2))-40=0
We calculate terms in parentheses: -(4(x+4)+4(x-2)), so:
4(x+4)+4(x-2)
We multiply parentheses
4x+4x+16-8
We add all the numbers together, and all the variables
8x+8
Back to the equation:
-(8x+8)
We get rid of parentheses
10x-8x-8-40=0
We add all the numbers together, and all the variables
2x-48=0
We move all terms containing x to the left, all other terms to the right
2x=48
x=48/2
x=24

See similar equations:

| 3x+5-x=3-(-6) | | 9h+45=8h | | 7x+32=5x | | 2+2x=14-x | | 50x+0=60x+60 | | 6(x-5)+4x=100 | | -24=9+3(c-6) | | 5=1/2d-3 | | 5d^2+15d+5=-6 | | y=6(45)+3 | | 7x+7=-9+5x | | a^2-15a+42=0 | | 1/7(4(x-1)=13)=x | | -63=-7(6+s) | | 1.6aa=1.2 | | 2m-3=5m | | 2+6n=-70 | | 45=6x+3 | | 4=-5b+b | | (3x+4x)=91 | | (J-6)=8h | | -2=3x-20÷4 | | -10(7n+2)=-10(9n+4) | | -8(t-4)-(t+8)=11 | | 7-5e=17 | | 1/3n-1/9=1/6n | | 60=15−5x | | (x-10)(3x+15)=300 | | 5-2(11+p)=1 | | 169=211-w | | 4x+3x-7=6x | | 75=-u+285 |

Equations solver categories